Grid-friendly photovoltaic systems via autonomous power reserve function - D'silva, Silvanus Ashok (Kansas State University, 2020)
The ever-increasing energy demand along with the depleting fossil fuel reserves and climate change has compelled the incorporation of renewables-based energy generation in the conventional power systems. Furthermore, the abundant availability of solar energy coupled with the rapid advances in photovoltaic (PV) technology and their low deployment and maintenance costs facilitate the large share of PV generated power amongst the total contribution from renewable generation. However, the intermittent nature of solar irradiation causes stability issues in the high PV penetrated grid. This limits the large-scale integration of PV sources in the power grid. A potential solution to address this issue is mitigation using energy storage systems. However, the downsides are the high cost, low reliability, and short lifetime of the currently available energy storage technologies. Another alternative to address these issues is by the implementation of clusters of PV sources interfaced to the grid and controlling them as a dispatchable generator via a microgrid (MG) framework. This minimizes the need of expensive energy storage systems for the mitigation of the power fluctuations and maintaining the grid stability. This thesis proposes an autonomous power reserve function (APRF) for the PV sources connected in a MG via a cluster architecture that enables grid friendly PV systems. The PV cluster architecture regulated by the APRF enables the mitigation of the source-side and the load side fluctuations experienced by the MG/ grid; thereby ensuring uninterrupted power fed to the local loads and a resilient operation of the entire system. The APRF regulates the operation set-point of the PV sources at a non-maximum power point and thus provides smooth PV power injection along with a dispatchable power reserve. Furthermore, this dispatchable reserve can be leveraged by the grid operator to maintain the voltage and frequency of the MG/grid in the event of a generation-demand imbalance. The proposed APRF functionality has been experimentally validated in a hardware-in-the-loop environment followed by a hardware implementation on gallium nitrite (GaN) based dc-dc boost converter. Besides, the proposed control scheme has been further modified to ensure injection of PV power into the grid occurs at a regulated ramp rate. This facilitates the regulation of grid frequency in a high PV penetrated grid environment. The proposed APRF functionality for the PV clusters shall enable the transformation of PV sources into a grid –friendly renewable based green and clean power source for the future.
Keywords: Grid-friendly photovoltaic systems; Adjustable power reserve; Power ramp rate control; Seamless transition in microgrids; High PV penetrated grid; Active power curtailment